Sea Surface Temperature and Wind Velocity in Batam Waters Its Relation to Indian Ocean Dipole (IOD) - Lubis, Muhammad Zainuddin; Anurogo, Wenang; Kausarian, Husnul; Surya, Ganda; Choanji, Tiggi (UIR PRESS, 2017)
This study aimed to observe the characteristics of sea surface temperature (SST) and wind velocity and its relation with the Indian Ocean Dipole (IOD) in the waters of Batam. The data used in this study were the SST datasets and the wind speed of 2016 in the waters of Batam. The method used in this research were the visual analysis using the data ocean view (ODV) to observe at the spatial and temporal distribution of the SST and the wind speed in Batam waters at different seasons. The next method is a fast Fourier transform (FFT). The earlier monsoon season that occurred in April has the highest wind speed with the value of 3.9 MS ** - 1 for components U. As for the V, the component has the highest value of -3.6 MS ** - 1. The SST Batam observed high in April occurred on 19-04-2016 with a value of 304.2 ° K (31.05 ° C). West monsoon winds that occurred in January has the highest wind speed with a value of 4.5 MS ** - 1 for components U. As for the V, the component has the highest value of 5.2 MS ** - 1 in the waters of Batam. The highest SST in Batam was  occurred in January on 19-01-2016 with a value of 302.8 ° K (29.65 ° C). Based on the results of the FFT, wind speed and SST in the waters of the Island has a dominant 6-month period (semiannual).